Lead contamination of soils, sediments, and vegetation in a shooting range and adjacent terrestrial and aquatic ecosystems: A holistic approach for evaluating potential risks. (April 2022) - Christou, Anastasis; Hadjisterkotis, Eleftherios; Dalias, Panagiotis; Demetriou, Eleni; Christofidou, Maria; Kozakou, Sofia; Michael, Nicos; Charalambous, Chrystalla; Hatzigeorgiou, Militsa; Christou, Eftychia; Stefani, Demetris; Christoforou, Evaggelia; et al.
Abstract: It is well accepted that shooting ranges constitute hotspots of Pb contamination. This study evaluated the degree of Pb contamination of soils, sediments and vegetation within the boundaries of a highly visited shooting range, as well as the fluvial transport and dispersal of Pb, and therefore the contamination of adjacent river and water reservoir. Soils in the shooting range were severely contaminated with Pb, as indicated by the values of enrichment and contamination factor. The concentration of Pb in these soils ranged from 791 mg kg −1 to 7265 mg kg −1, being several dozens or even hundreds of times higher compared with control background samples. A temporary stream being in close proximity was also polluted, though to a much lesser extent. The degree of Pb contamination was negatively correlated with the distance from the shooting range. To this effect, the degree of contamination of the river and the water reservoir being in the vicinity of the shooting range was negligible, as sediments and water samples preserved similar Pb concentrations with control samples. However, cultivated (olives) and wild native plant species grown in the area of the shooting range were found to uptake and accumulate high concentrations of Pb in their tissues (even 50 times higher compared with control samples). The severe contamination of soils, sediments and vegetation in the studied shooting range can provoke very high ecological risks. Overall, results suggest that management measures should be undertaken within the boundaries of the studied shooting range. Graphical abstract: Image 1 Highlights: Pb in soil, sediments and vegetation in the vicinity of shooting range was studied. Soils and sediments in the shooting range were severely contaminated with Pb. Cultivated and wild plants accumulated increased amounts of Pb. Fluvial transport in adjacent river and water reservoir was negligible. Pb contamination in the shooting range can provoke very high ecological risks.